Immediate Antiretroviral Therapy Reduces Risk of Infection-Related Cancer During Early HIV Infection. (8th September 2016) - Borges, Álvaro H.; Neuhaus, Jacqueline; Babiker, Abdel G.; Henry, Keith; Jain, Mamta K.; Palfreeman, Adrian; Mugyenyi, Peter; Domingo, Pere; Hoffmann, Christian; Read, Tim R. H.; Pujari, Sanjay; Meulbroek, Michael; et al.
Abstract : In Strategic Timing of Antiretroviral Treatment, immediate combination antiretroviral therapy (cART) reduced risk of infection-related cancer by 74% and infection-unrelated cancer by 51%. The benefit of immediate cART doesn't appear to be solely attributable to human immunodeficiency virus RNA suppression and may also be mediated by other mechanisms. Abstract : Background: In the Strategic Timing of Antiretroviral Treatment (START) study, immediate combination antiretroviral therapy (cART) initiation reduced cancer risk by 64%. We hypothesized that risk reduction was higher for infection-related cancer and determined by differences in CD4 cell counts and human immunodeficiency virus (HIV) RNA between the study arms. Methods: Incident malignancies in START were categorized into infection-related and infection-unrelated cancer. We used Cox models to assess factors associated with both cancer categories. We used sequential adjustment for baseline covariates, cancer risk factors, and HIV-specific variables to investigate potential mediators of cancer risk reduction with immediate cART. Results: There were 14 cancers among persons randomized to immediate cART (6 infection-related and 8 infection-unrelated) and 39 cancers in the deferred arm (23 infection-related and 16 infection-unrelated); hazard ratios of immediate vs deferred cART initiation were 0.26 (95% confidence interval [CI], .11–.64) for infection-related and 0.49 (95% CI, .21–1.15) for infection-unrelated cancer. Independent predictors of infection-related cancer were older age, higher body mass index, low- to middle-income region, HIV RNA, and baseline CD8 cell count. Older age and baseline CD8 cell count were independent predictors of infection-unrelated cancer. Adjustment for latest HIV RNA level had little impact on the protective effect of immediate cART on infection-related cancer. Adjustment for latest HIV RNA level, but not for CD4 cell count or cancer risk factors, attenuated the effect of immediate cART on infection-unrelated cancer. Conclusions: Immediate cART initiation significantly reduces risk of cancer. Although limited by small sample size, this benefit does not appear to be solely attributable to HIV RNA suppression and may be also mediated by other mechanisms.